2015
DOI: 10.1038/onc.2015.210
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes promote glioma invasion via the gap junction protein connexin43

Abstract: Reactive astrocytes are integral to the glioma microenvironment. Connexin43 (Cx43) is a major gap junction protein in astrocytes and its expression is enhanced significantly in glioma-associated astrocytes, especially at the peri-tumoral region. Although downregulation of Cx43-mediated intercellular communication is associated with increased malignancy in tumor cells, the role of Cx43 in stromal cells in glioma progression is not defined. Using a mouse model consisting of syngeneic intracranial implantation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
113
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(134 citation statements)
references
References 126 publications
7
113
2
3
Order By: Relevance
“…Expression of Cx43 is significantly enhanced in tumor-associated astrocytes especially at the region adjacent to the tumor core [11 •• ]. Recent reports suggest that astrocytic Cx43 may contribute to TMZ resistance in addition to enhancing GBM cell proliferation and migration.…”
Section: Connexin43 Channels In the Glioma Microenvironmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Expression of Cx43 is significantly enhanced in tumor-associated astrocytes especially at the region adjacent to the tumor core [11 •• ]. Recent reports suggest that astrocytic Cx43 may contribute to TMZ resistance in addition to enhancing GBM cell proliferation and migration.…”
Section: Connexin43 Channels In the Glioma Microenvironmentmentioning
confidence: 99%
“…In a co-culture system of human astrocytes and tumor cells designed to simulate the tumor microenvironment, siRNA knockdown of astrocytic Cx43 abolished GJIC between glioma cells and astrocyte and increased TMZ-induced apoptosis of GBM cells [42]. Furthermore, in a mouse model consisting of syngeneic intracranial implantation of GL261 malignant glioma cells into Nestin-Cre:Cx43 fl/fl mice, in which Cx43 is selectively eliminated in astrocytes, it was demonstrated that reduction of astrocytic Cx43 decreases the invasion of tumor cells from the tumor core in the presence of an intact immune system [11 •• ]. The importance of astrocytic Cx43 in the regulation of GBM resistance and in tumor invasiveness strongly supports the manipulation of Cx43 in the GBM microenvironment as a promising therapeutic strategy in controlling glioma.…”
Section: Connexin43 Channels In the Glioma Microenvironmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Cx43 is widely expressed in adult astrocytes and exhibits increased expression in reactive astrocytes induced by various brain pathologies and intercellular calcium signaling [67][68][69][70][71][72][73]. Also, Cx43-mediated intercellular communication between astrocytes plays an important role in the invasion of glioma cells in the brain [63].…”
Section: Astrocytes' Direct Cell-cell Interactions With Tumor Cellsmentioning
confidence: 99%
“…The proliferative dysfunction and invasion of gliomas are associated with changes in gap junction communication [62,63]. In metastatic brain tumors, reactive astrocytes protect melanoma cells from chemotherapy induced cell death by sequestering intracellular calcium through gap junctions [64].…”
Section: Astrocytes' Direct Cell-cell Interactions With Tumor Cellsmentioning
confidence: 99%